Structural and Functional Characterization of a New Double Variant Haemoglobin (HbG-Philadelphia/Duarte α268Asn→Lysβ262Ala→Pro). (3rd November 2010) - Fais, Antonella; Casu, Mariano; Ruggerone, Paolo; Ceccarelli, Matteo; Porcu, Simona; Era, Benedetta; Anedda, Roberto; Sollaino, Maria Carla; Galanello, Renzo; Corda, Marcella
Abstract : We report the first case of cosegregation of two haemoglobins (Hbs): HbG-Philadelphia [α 68(E17) Asn → Lys ] and HbDuarte [β 62(E6) Ala → Pro ]. The proband is a young patient heterozygous also forβ ∘ -thalassaemia. We detected exclusively two haemoglobin variants: HbDuarte and HbG-Philadelphia/Duarte. Functional study of the new double variant HbG-Philadelphia/Duarte exhibited an increase in oxygen affinity, with a slight decrease of cooperativity and Bohr effect. This functional behaviour is attributed toβ 62 Ala → Pro instead ofα 68 Asn → Lys substitution. Indeed, HbG-Philadelphia isolated in our laboratory from blood cells donor carrier for this variant is not affected by any functional modification, whereas purified Hb Duarte showed functional properties very similar to the double variant. NMR and MD simulation studies confirmed that the presence of Pro instead of Ala at theβ 62 position produces displacement of the E helix and modifications of the tertiary structure. The substitutionα 68(E17) Asn → Lys does not cause significant structural and dynamical modifications of the protein. A possible structure-based rational of substitution effects is suggested.